2012
DOI: 10.4040/jkan.2012.42.2.291
|View full text |Cite
|
Sign up to set email alerts
|

Homebound status and Related Factors According to Age in Female Elders in the Community

Abstract: Purpose: The purpose of this study was to investigate homebound status and significant related factors for community-dwelling female elders according to age. Methods: The participants were female elders over 65 years of age registered in public health centers. Data were collected by interviewing the elders, who voluntarily completed the entire survey. For data analysis, descriptive statistics and multiple logistic regression were performed using SPSS version 18.0. Results: There were statistically significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 19 publications
1
13
0
3
Order By: Relevance
“…With the increase in age, the prevalence of homebound increases gradually. Studies [18] have found that nearly 30% of the homebound people are aged ≥80 years. Physiological function and social activity ability weakened with the increase in age, [19,20] leading to a gradual increase in the occurrence of elderly homebound.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the increase in age, the prevalence of homebound increases gradually. Studies [18] have found that nearly 30% of the homebound people are aged ≥80 years. Physiological function and social activity ability weakened with the increase in age, [19,20] leading to a gradual increase in the occurrence of elderly homebound.…”
Section: Discussionmentioning
confidence: 99%
“…Many overseas studies have found that the prevalence of homebound women is significantly higher than men. The reasons could be complex, [18,21] which may be due to diet habits, sexual hormone levels, work stress, and social pressure, and also due to the profound influence on their behaviors by the traditional role of a man and a woman in the family, that is, men are encouraged to work outside, while women are encouraged to work at home. Hence men preferred social activities outside the family, while women focused more on family and children and stayed at home.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical experience suggests that home confinement is a common problem in the everyday life of people with major disabilities, particularly in people with limited basic ADLs. Homebound status has been associated with loneliness, 1 depression, [1][2][3][4][5] comorbidity, 1,6 hospitalization, 4,7 and worse self-reported health status 1,8 ; moreover, it is a risk factor for mortality. 3,7,8 Previous research has estimated the prevalence of homebound status in the older population, 1,4,[8][9][10][11] using diverse definitions.…”
mentioning
confidence: 99%
“…또한 이들은 경제적으로 빈곤할 뿐만 아니라 가족 및 사회적 지지체계와 단절되어 있는데, 대규모 조사연구에 따르면 약 37%의 독거노인은 칩거하고 있으며 [5], 16%는 가족 또는 이웃 과 연 1 이하의 연락을 유지하고 있다 [2]. 이러한 사회적 고립은 삶의 질을 저하시키고 우울 [6,7] 및 자살 [8,9] …”
unclassified